Developing Infographics to Teach Speaking Through CakeApp for Tourism Students - Sasmitha, Ketut Aya; Utami, Iga Lokita Purnamika; Agustini, Dewa Ayu Eka (Journal of English Language and Education, 2025)
Enhancing students' speaking abilities requires integrating technology into language training, particularly in professional settings like tourism. For vocational high school (SMK) students working in the tourism industry, speaking is an essential skill because they must be able to interact with foreign tourists. The goal of this project is to create infographics based on CakeApp that will help Grade XII tourism students at Buleleng's vocational high schools learn how to speak. The study uses Richey Klein, (2005) Design and Development (DD) framework in conjunction with the ADDE (Analysis, Design, Development, Evaluation) model. The end result is a collection of infographics made to help teachers of English incorporate CakeApp into their speaking lessons. With an average score of 91.5%, expert validation results show that the infographics are of extremely high quality. These results imply that infographics based on CakeApp successfully improve students' speaking practice. From a practical standpoint, the product provides teachers at tourism vocational schools with an invaluable teaching tool.